A composite cementitious material, preparation method and application thereof
By combining activated carbon obtained by pyrolysis of coffee grounds with cement to form a composite gelling material, the problem of poor adsorption effect of heavy metal ions in the prior art is solved, efficient adsorption and removal of heavy metal ions is achieved, and environmental pollution and threats to human health are reduced.
Patent Information
- Application Number
- CN202410306589.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-18
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-03-18
AI Technical Summary
The prior art has poor adsorption effect on the surface of roads or buildings and accumulated heavy metal ions, and may cause serious secondary pollution.
The activated carbon prepared by pyrolysis of coffee grounds is combined with cement to form a composite cementitious material for adsorption of heavy metal ions. The pore structure and functional groups of activated carbon in this material can significantly improve the adsorption capacity of heavy metal ions and form an alkaline environment during the hydration process, further promoting the removal of heavy metal ions.
It realizes efficient adsorption and removal of heavy metal ions, reduces environmental pollution and potential threats to human health, and maintains the good mechanical properties of the gelled materials.
Smart Images

Figure CN118164723B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a composite cementitious material, a preparation method and application thereof. Background Art
[0002] The rapid development of the construction industry is a sign of social progress. However, although the rapid development of the construction industry can promote the development of urban modernization, it will also pollute the urban environment and endanger human health.
[0003] In the construction field, such as the production of construction materials, anti-rust treatment of steel bars, house decoration and painting, and foundation material production, chromium ions and lead ions are widely used heavy metal ions. The heavy metal ions used in foundations and building materials will subsequently settle on the surface of roads or buildings, and seep into the surface of buildings or water sources with the erosion of rainwater, which will not only affect the quality of the project, pollute the urban environment, but also endanger human health. In addition, buildings will be polluted by wastewater, waste gas, and waste residues when they exist for a long time, and heavy metal ions will accumulate on the surface of the base. These heavy metal ions will also migrate and spread to the environment with the erosion of rainwater, which will also cause environmental pollution and affect human health.
[0004] In the prior art, heavy metal ions that have seeped out of roads or building surfaces and accumulated are generally adsorbed by reduction, reverse osmosis, electrodialysis, and ion exchange methods, etc. However, the above methods have poor adsorption effects on heavy metal ions and may even cause serious secondary pollution.
[0005] Therefore, it is necessary to provide a material or method with better ability to remove heavy metal ions that have seeped and accumulated on the surface of roads or buildings, so as to reduce environmental pollution and potential threats to human health. Summary of the invention
[0006] 1. Technical issues to be resolved
[0007] In view of the above technical problems, in order to solve the problem that the existing adsorption methods have poor treatment effects on the extravasation and accumulation of heavy metal ions on roads or building surfaces, the present invention provides a composite gelling material, a preparation method and application thereof.
[0008] (II) Technical solution
[0009] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0010] In a first aspect, the present invention provides a composite cementitious material, comprising cement and activated carbon; the composite cementitious material comprises 40-60% of activated carbon by mass; the activated carbon is prepared by pyrolysis of coffee grounds.
[0011] The composite gelling material as described above, preferably, comprises 50-60% of activated carbon by mass.
[0012] In a second aspect, the present invention further provides a method for preparing the composite cementitious material, comprising the following steps:
[0013] S1: adding phosphoric acid solution to coffee grounds for activation treatment to obtain activated coffee grounds;
[0014] S2: Pyrolyzing the activated coffee grounds in an oxygen-free environment to obtain pyrolyzed activated carbon;
[0015] S3: grinding the pyrolytic activated carbon to obtain pyrolytic activated carbon powder;
[0016] S4: mixing the pyrolytic activated carbon powder with cement to obtain a composite cementitious material; wherein, by mass fraction, the pyrolytic activated carbon powder accounts for 40-60% of the composite cementitious material.
[0017] In the preparation method as described above, preferably, in step S1, the activation treatment time is 18-30 hours; the mass ratio of coffee grounds to phosphoric acid solution is 1:2-1:4, and the mass concentration of phosphoric acid solution is 40-60%.
[0018] In the preparation method as described above, preferably, in step S2, the temperature is raised to 450-550° C. at a rate of 5-10° C. / min in an oxygen-free environment and kept warm for 2-3 hours.
[0019] In the preparation method as described above, preferably, before step S1, the coffee grounds are cleaned and then dried; after step S2 and before step S3, the pyrolytic activated carbon is also washed and then dried.
[0020] In the preparation method as described above, preferably, in step S3, the pyrolytic activated carbon is ground and passed through a 50-200 mesh sieve to obtain pyrolytic activated carbon powder.
[0021] In a third aspect, the present invention also provides an application of the above-mentioned composite cementitious material or the composite cementitious material prepared by the above-mentioned preparation method. The composite cementitious material is mixed with aggregate to form an adsorbent, and the adsorbent is arranged on the surface of a building and / or a road to adsorb heavy metal ions that have seeped out of the building and / or the road.
[0022] In the above application, preferably, the heavy metal ions include Cr 6+ and Pb 2+ .
[0023] (III) Beneficial effects
[0024] The present invention partially replaces cement with activated carbon prepared by pyrolysis of coffee grounds. The obtained composite cementitious material has good adsorption performance for heavy metal ions and can be arranged on the surface of roads or buildings to well adsorb heavy metal ions that have seeped and accumulated on the surface of roads or buildings.
[0025] In the present invention, the surface of the activated carbon prepared by pyrolysis of coffee grounds is loose and porous, has a good pore structure, and can provide abundant heavy metal ion adsorption sites. In addition, the surface of the activated carbon prepared by pyrolysis of coffee grounds also contains abundant functional groups such as carboxyl, hydroxyl, and amino groups, which have good affinity for heavy metal ions and can significantly improve the adsorption capacity of heavy metal ions.
[0026] The activated carbon prepared by pyrolysis of coffee grounds is combined with cement at a ratio of 40-60%, which can not only ensure the good mechanical properties of the cementitious material, but also produce hydroxide hydration products during the hydration process of the composite cementitious material formed by cement and activated carbon, forming an alkaline environment. 6+ Usually Cr2O7 2- (dichromate) exists in the form of Cr 6+ In this alkaline environment, a minimally harmful Cr(III) precipitate is solidified. Similarly, in this alkaline environment, Pb 2+ It can also generate white precipitate to achieve better removal effect.
[0027] In addition, after the activated carbon prepared by pyrolysis of coffee grounds is mixed with cement, it can also store a small amount of free water through its rich pore structure. After the initial hydration is completed, the free water stored in the pore structure can continue to flow out in small amounts, continue to promote the hydration reaction of cement, and continuously and stably remove heavy metal ions.
[0028] Therefore, the composite gelling material of the present invention can achieve long-term and stable adsorption and removal of heavy metal ions through the synergistic effect of multiple adsorption mechanisms. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the TG-DTG curve obtained by burning coffee grounds in air atmosphere;
[0030] Figure 2 The composite gelling material obtained in Example 1 and Comparative Example 1 adsorbs Cr 6+ FTIR images before and after;
[0031] Figure 3 The composite gelling material obtained in Example 1 and Comparative Example 1 adsorbs Pb 2+ FTIR images before and after;
[0032] Figure 4 1 and 2 are BET diagrams of the composite cementitious materials obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0033] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with specific implementation methods.
[0034] The invention provides a composite cementitious material, comprising cement and activated carbon prepared by pyrolysis of coffee grounds. According to mass fraction, the composite cementitious material comprises 40-60% of activated carbon.
[0035] Preferably, the composite gel material comprises 50-60% activated carbon by mass.
[0036] The present invention also provides a method for preparing the composite gelling material, comprising the following steps:
[0037] S1: Add phosphoric acid solution to coffee grounds for activation treatment to obtain activated coffee grounds. Activating coffee grounds with phosphoric acid can remove grease on the surface of the coffee grounds, which is beneficial to pyrolysis and can also enrich the functional groups on the surface of activated carbon after pyrolysis.
[0038] S2: Pyrolysis treatment of activated coffee grounds in an oxygen-free environment to obtain pyrolysis activated carbon. In this step, the role of pyrolysis treatment is to increase the pore size of activated carbon and make the pore structure of activated carbon richer, so as to increase the specific surface area and adsorption capacity of activated carbon. In addition, the surface of activated carbon after pyrolysis treatment also contains abundant functional groups such as carboxyl, hydroxyl, and amino groups, which have good affinity for heavy metal ions and can significantly improve the adsorption capacity of heavy metal ions.
[0039] S3: Grinding the pyrolyzed activated carbon to obtain pyrolyzed activated carbon powder.
[0040] S4: Mixing pyrolyzed activated carbon powder with cement to obtain a composite cementitious material; wherein, in terms of mass fraction, the pyrolyzed activated carbon powder accounts for 40-60% of the composite cementitious material. Further preferably, the pyrolyzed activated carbon powder accounts for 50-60% of the composite cementitious material. In this step, the proportion of the pyrolyzed activated carbon powder in the composite cementitious material will directly affect the composite cementitious material's ability to adsorb and remove heavy metal ions. When the pyrolyzed activated carbon powder accounts for less than 40% of the total amount of the composite cementitious material, the composite cementitious material's ability to adsorb and remove heavy metal ions will be significantly reduced. In addition, keeping the pyrolyzed activated carbon powder at 40-60% of the composite cementitious material can also enable the composite cementitious material to maintain good mechanical properties. If the pyrolyzed activated carbon powder accounts for more than 60%, the composite cementitious material will find it difficult to maintain its shape.
[0041] The present invention uses waste coffee grounds as raw materials to prepare activated carbon, making full use of waste biological resources. Compared with commercial activated carbon, a non-renewable material, it implements the environmental protection concept of "solid waste utilization", which is low-cost, economical and environmentally friendly.
[0042] In the above step S1, the activation treatment time is 18-30 hours, the mass ratio of coffee grounds to phosphoric acid solution is 1:2-1:4, preferably 1:3, the mass concentration of phosphoric acid solution is 40-60%, preferably 50%, and the activation treatment time is preferably 24-36 hours. Before step S1, the coffee grounds can be washed with deionized water to remove dust and other impurities on the surface, and then the coffee grounds are dried at 85-105°C.
[0043] In step S2, specifically, the temperature is raised to 450-550°C at a rate of 5-10°C / min in an oxygen-free environment, kept at this temperature for 2-3 hours to complete the pyrolysis treatment, and then cooled to room temperature.
[0044] After step S2 and before step S3, the pyrolytic activated carbon obtained in step S2 is washed multiple times with deionized water to remove phosphoric acid therein, and then dried at 85-105°C.
[0045] In step S3, the dried pyrolytic activated carbon is ground and passed through a 50-200 mesh sieve to obtain pyrolytic activated carbon powder, which can be sealed in a drying container for later use.
[0046] The present invention also provides the use of the composite cementitious material or the composite cementitious material prepared by the above preparation method. The composite cementitious material is mixed with aggregate to form an adsorbent, which can be set on the surface of buildings and / or roads to adsorb heavy metal ions that have seeped out of buildings and / or roads. The heavy metal ions include Cr 6+ and Pb 2+ .
[0047] In the above application, the composite cementitious material can also be mixed with aggregates, such as sand and stone, to form a concrete adsorbent. The addition of sand and stone can further improve the strength of the adsorbent without affecting the adsorption performance of heavy metal ions. The composite cementitious material adsorbent or concrete adsorbent can be used as a decorative wall or curbstone.
[0048] The composite gelling material of the present invention can achieve long-term and stable adsorption and removal of heavy metal ions through the synergistic effect of the following three adsorption mechanisms:
[0049] First, the activated carbon obtained by pyrolysis of coffee grounds has a loose and porous surface and a good pore structure, which can provide abundant heavy metal ion adsorption sites and ensure the adsorption effect of heavy metal ions.
[0050] Second, the surface of activated carbon obtained by pyrolysis of coffee grounds also contains abundant functional groups such as carboxyl, hydroxyl, and amino groups. These functional groups have good affinity for heavy metal ions and can significantly improve the adsorption capacity of heavy metal ions.
[0051] Third, the composite cementitious material formed by combining the activated carbon obtained by pyrolysis of coffee grounds with cement at a ratio of 40-60% will produce hydroxide hydration products during the hydration process, forming an alkaline environment. 6+ Usually Cr2O7 2- In the form of Cr 6+ In this alkaline environment, a minimally harmful Cr(III) precipitate will be formed and solidified and removed. 2+ White precipitate can also be generated in an alkaline environment, achieving better removal effect.
[0052] In addition, the rich pore structure of activated carbon can further maintain the above alkaline environment for a long time: the pore structure of activated carbon obtained by pyrolysis of coffee grounds can store free water. After the initial hydration of the composite cementitious material is completed, the free water stored in the pore structure can flow out in small amounts continuously, further promoting the hydration reaction of cement and continuously maintaining the alkaline environment, so that heavy metal ions can be removed continuously and stably. In addition, in the subsequent application process, the pore structure of activated carbon can still continuously store free water and continue to flow out, promoting the hydration reaction of cement, so as to remove heavy metal ions stably and long-term.
[0053] Cr 6+ and Pb 2+ The removal principle in an alkaline environment is as follows:
[0054] Pb+2OH - →Pb(OH)2↓+2e
[0055] Cr2O7 2- +2OH - =2CrO4 2- +H2O
[0056] CrO4 2- +4H2O+3e=Cr(OH)↓+5OH -
[0057] Example 1
[0058] This embodiment provides a method for preparing a composite gelling material, comprising the following steps:
[0059] S1: Rinse the waste coffee grounds with deionized water. After rinsing, use a water circulation vacuum pump to filter the cleaned coffee grounds, and then place them in a drying oven at 105°C for 12 hours.
[0060] S2: Keeping the solid-liquid ratio at 1:3, add the dried coffee grounds into phosphoric acid with a mass concentration of 50% and soak for 24 hours, stirring at a fixed frequency during the soaking process to obtain activated coffee grounds.
[0061] S3: Put the activated coffee grounds into a muffle furnace, raise the temperature to 450°C at a heating rate of 8°C / min under anaerobic environment, and then maintain this temperature for 2 hours to obtain pyrolytic activated carbon (AC), which is then filtered and cleaned with a water circulation vacuum pump until the washing liquid is neutral, and finally placed in an oven and dried at 105°C.
[0062] S4: The dried pyrolytic activated carbon is placed in a pulverizer for crushing and then passed through a 200-mesh sieve, and the obtained pyrolytic activated carbon powder is collected in a sealed container.
[0063] S5: Weigh the sieved pyrolytic activated carbon powder and pour it into a stirring pot for standby use, then weigh cement and pour it into the stirring pot for dry mixing to obtain a composite cementitious material, wherein the mass ratio of the pyrolytic activated carbon powder in the composite cementitious material is 60%.
[0064] Example 2
[0065] This embodiment provides a method for preparing a composite gelling material, comprising the following steps:
[0066] S1: Rinse the waste coffee grounds with deionized water. After rinsing, use a water circulation vacuum pump to filter the cleaned coffee grounds, and then place them in a drying oven at 85°C to dry for 12 hours.
[0067] S2: Keeping the solid-liquid ratio at 1:2, add the dried coffee grounds into phosphoric acid with a mass concentration of 60% and soak for 28 hours, stirring at a fixed frequency during the soaking process to obtain activated coffee grounds.
[0068] S3: Put the activated coffee grounds into a muffle furnace, raise the temperature to 500°C at a heating rate of 10°C / min under anaerobic environment, and then maintain it at this temperature for 3 hours to obtain pyrolytic activated carbon, which is then filtered and cleaned with a water circulation vacuum pump until the washing liquid is neutral, and finally placed in an oven and dried at 85°C.
[0069] S4: The dried pyrolytic activated carbon is placed in a pulverizer and crushed, and then passed through a 150-mesh sieve, and the obtained pyrolytic activated carbon powder is collected in a sealed container.
[0070] S5: Weigh the sieved pyrolytic activated carbon powder and pour it into a stirring pot for standby use, then weigh cement and pour it into the stirring pot for dry mixing to obtain a composite cementitious material, wherein the mass ratio of the pyrolytic activated carbon powder in the composite cementitious material is 40%.
[0071] Example 3
[0072] This embodiment provides a method for preparing a composite gelling material, comprising the following steps:
[0073] S1: Rinse the waste coffee grounds with deionized water. After rinsing, use a water circulation vacuum pump to filter the cleaned coffee grounds, and then place them in a drying oven at 95°C to dry for 12 hours.
[0074] S2: Keeping the solid-liquid ratio at 1:4, add the dried coffee grounds into phosphoric acid with a mass concentration of 40% and soak for 36 hours, stirring at a fixed frequency during the soaking process to obtain activated coffee grounds.
[0075] S3: Put the activated coffee grounds into a muffle furnace, raise the temperature to 550°C at a heating rate of 5°C / min under anaerobic environment, and then maintain it at this temperature for 2.5 hours to obtain pyrolytic activated carbon, which is then filtered and cleaned with a water circulation vacuum pump until the washing liquid is neutral, and finally placed in an oven and dried at 95°C.
[0076] S4: Put the dried pyrolytic activated carbon into a pulverizer for crushing and then pass it through a 100-mesh sieve, and collect the obtained pyrolytic activated carbon powder in a sealed container.
[0077] S5: Weigh the sieved pyrolytic activated carbon powder and pour it into a stirring pot for standby use, then weigh cement and pour it into the stirring pot for dry mixing to obtain a composite cementitious material, wherein the mass ratio of the pyrolytic activated carbon powder in the composite cementitious material is 50%.
[0078] Example 4
[0079] This embodiment provides a method for preparing a composite gelling material, which is different from Embodiment 1 in that the mass ratio of the pyrolyzed activated carbon powder in the composite gelling material is 55%.
[0080] Comparative Example 1
[0081] The difference between Comparative Example 1 and Example 1 is that the mass ratio of the pyrolyzed activated carbon powder in the composite gelling material is 0%.
[0082] Comparative Example 2
[0083] The difference between this comparative example and Example 1 is that the mass ratio of the pyrolyzed activated carbon powder in the composite gelling material is 20%.
[0084] Performance Test:
[0085] Water was added to the composite cementitious materials obtained in each embodiment and comparative example at a water-cement ratio of w / c=0.5, and the mixture was stirred evenly to prepare a 25mm×25mm×25mm test piece. After demoulding the next day, the test piece was cured in a standard curing room for 28 days. The cured test piece was placed in the prepared initial Cr 6+ The concentration is 300 mg / L and the initial Pb 2+ Soak in a solution with a concentration of 300 mg / L for 48 hours, and take the supernatant to detect the concentration of heavy metal ions.
[0086] Specifically, 10 ml of the supernatant after adsorption of the test pieces of Examples 1-4 and Comparative Examples 1-2 was extracted with a syringe, and the supernatant was filtered with a 0.45 um filter membrane. Three parallel samples were set for each Example and Comparative Example, and Cr was measured by inductively coupled plasma atomic emission spectrometry (ICP-AES). 6+ and Pb 2+ The experimental results take the average value of the three groups of test data, and calculate the removal rate and adsorption amount of heavy metal ions. The calculation formulas for removal rate and adsorption amount are as follows:
[0087]
[0088] q=(C0-C e )V / m
[0089] Where: η is the removal rate of heavy metals in the solution, in %; q is the adsorption amount of the specimen, in mg / g; C0 is the initial concentration of heavy metals in the solution, in mg / L; C e is the equilibrium mass concentration of heavy metals in the solution, in mg / L; V is the volume of the solution, in L; m is the mass of the composite gelling material, in mg. The removal rate and adsorption amount of heavy metal ions are shown in Table 1 and Table 2.
[0090] Table 1 Examples 1-4 and Comparative Examples 1-2 for Cr 6+ Removal rate and adsorption capacity data table
[0091]
[0092] Table 2 Table 1 Examples 1-4 and Comparative Examples 1-2 for Pb 2+ Removal rate and adsorption capacity data table
[0093]
[0094]
[0095] From Table 1 and Table 2, it can be seen that the composite cementitious materials of Examples 1-4 have an influence on Cr 6+ and Pb2+ It has a good adsorption effect. The initial solution contains Cr 6+ The concentration is 300mg / L, Pb 2+ The concentration is also 300 mg / L. 6+ and Pb 2+ The concentration is higher than the concentration of heavy metal ions that seep out or accumulate on the surface of roads and buildings in actual applications. Therefore, when the composite cementitious material is set on the surface of buildings and / or roads, the Cr 6+ and Pb 2+ The adsorption effect is better than that in Table 1 and Table 2. When the removal rate of heavy metal ions in Table 1 and Table 2 reaches 60% or above, the content of heavy metal ions can be reduced to below the standard range in actual application.
[0096] In addition, the temperature at which the carbon rate is appropriate was determined using a synchronous thermal analyzer (PerKinELmer STA 8000) from the United States, the surface functional groups of the composite gelling materials obtained in Example 1 and Comparative Example 2 were tested using a Nicolet iS10 Fourier transform infrared spectrometer, and the specific surface area of the composite gelling materials obtained in Example 1 and Comparative Example 1 was analyzed using a fully automatic specific surface and porosity analyzer (BET) from Micromeritics ASAP 2460 from the United States.
[0097] TG-DTG analysis:
[0098] In air atmosphere, at 15℃·min -1 The heating rate is to burn the coffee grounds and obtain Figure 1 The TG-DTG curve shown in FIG. 1 shows the relationship between the weight of coffee grounds and the temperature, and the DTG curve is obtained by taking the derivative of the TG curve with respect to time. Figure 1 It can be seen that the combustion of coffee grounds can be divided into three stages: Stage I (<200℃) is the water evaporation stage, Stage II (200℃-450℃) is the mass combustion stage, and Stage III (>450℃) is the burnout stabilization stage. In Stage III, only the residual ash is burned.
[0099] In the DTG curve, there is a weight loss peak representing water evaporation in stage I, three weight loss peaks in stage II, and stability is achieved in the third stage. Therefore, it can be concluded that the activated carbon obtained by firing coffee grounds at 450℃-550℃ has the best performance.
[0100] Fourier Transform Infrared Spectroscopy (FTIR) Analysis:
[0101] The surface functional groups of the composite gelling materials obtained in Example 1 and Comparative Example 1 were tested by using Nicolet iS10 Fourier transform infrared spectrometer. In addition, the surface functional groups of the composite gelling materials obtained in Example 1 and Comparative Example 1 after adsorbing heavy metal ions were tested, and the surface functional groups were obtained respectively. Figure 2 as well as Figure 3 .
[0102] Figure 2 as well as Figure 3 The stretching vibration peaks of free hydroxyl groups appear at 3422 cm -1 and 3424cm -1 At 0%, the free hydroxyl groups in the material with pyrolytic activated carbon powder content mainly come from the crystal water attached to the hydration product in the cement test block. The peak of the composite cementitious material with pyrolytic activated carbon content of 60% is strengthened. This is because the activated carbon itself contains rich hydroxyl functional groups and has a certain positive effect on cement hydration. However, after adsorbing heavy metal ions, it can be seen from the AC (60%)-Cr / Pb curve that the absorption peak is weakened. This is because the hydroxyl functional groups form coordination compounds with heavy metal ions to a large extent, realizing the adsorption and removal of heavy metal ions.
[0103] pass Figure 2 as well as Figure 3 It can be seen that the absorption band is at 1633cm -1 1641cm -1 The structure of amide carbon-oxygen double bond (C=O) is at the center, and the absorption peak of AC(60%) is higher than that of AC(0%). This may be due to the fact that there are more amides caused by the organic matter and protein contained in the pyrolyzed activated carbon. However, there is a weakening trend in AC(60%)-Cr / Pb, which may be because heavy metal ions will combine with amides to destroy the carbon-oxygen double bonds.
[0104] pass Figure 2 as well as Figure 3 It can be seen that the absorption band is at 1428cm -1 1429cm -1 The absorption vibration peak of carbonate ions is at the center. Compared with AC(0%), the absorption peak of AC(60%) is stronger. This is due to the influence of abundant carbonate functional groups in pyrolyzed activated carbon. In the AC(60%)-Cr / Pb curve, the peak shows a weakening trend, which may be due to the reaction with heavy metal ions, consuming carbonate.
[0105] From the above content, it can be seen that the rich functional groups contained in activated carbon can further increase the adsorption sites of heavy metal ions.
[0106] BET Analysis:
[0107] After testing, we obtained Figure 4 The BET comparison diagram of the composite gelling material obtained in Example 1 and Comparative Example 1 is shown, wherein the upper right corner is a partial enlarged diagram of the BET comparison diagram of the composite gelling material obtained in Example 1 and Comparative Example 1. Figure 4 It can be seen that the pore capacity of the composite gelling material with 60% pyrolytic activated carbon added in Example 1 is slightly smaller than that of the composite gelling material with 0% pyrolytic activated carbon added in Comparative Example 1. However, according to the above analysis, the adsorption capacity of the composite gelling material with 60% pyrolytic activated carbon added to heavy metal ions is much higher than that of the composite gelling material with 60% pyrolytic activated carbon added, indicating that in the present invention, the pore structure providing heavy metal ion adsorption sites for adsorption is not the only adsorption mechanism of the composite gelling material in the present invention, and functional group adsorption and chemical adsorption after hydration to form an alkaline environment can play a very critical role in the adsorption process.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite gelling material for use in adsorbing heavy metal ions that have seeped out of buildings and / or roads, characterized in that: The composite cementitious material comprises cement and activated carbon; in terms of mass fraction, the composite cementitious material comprises 40-60% of activated carbon; the composite cementitious material is mixed with aggregate to form an adsorbent, and the adsorbent is arranged on the surface of a building and / or a road to adsorb the infiltrated heavy metal ions; the heavy metal ions include Cr 6+ and Pb 2+ ; The activated carbon is prepared by pyrolysis of coffee grounds and contains carboxyl, hydroxyl and amino functional groups on its surface; The preparation method of the composite cementitious material comprises the following steps: S1: adding phosphoric acid solution to coffee grounds for activation treatment to obtain activated coffee grounds; the activation treatment time is 18-30 hours; the mass ratio of coffee grounds to phosphoric acid solution is 1:2-1:4, and the mass concentration of phosphoric acid solution is 40-60%; S2: Pyrolyzing the activated coffee grounds in an anaerobic environment to obtain pyrolyzed activated carbon; specifically, heating the mixture to 450-550°C at a rate of 5-10°C / min in an anaerobic environment and keeping the temperature for 2-3 hours; S3: grinding the pyrolytic activated carbon to obtain pyrolytic activated carbon powder; S4: mixing the pyrolyzed activated carbon powder with cement to obtain a composite cementitious material; wherein, by mass fraction, the pyrolyzed activated carbon powder accounts for 40-60% of the composite cementitious material.
2. The use according to claim 1, characterized in that: According to the mass fraction, the composite gel material includes 50-60% activated carbon.
3. The use according to claim 1, characterized in that: Before step S1, the coffee grounds are cleaned and then dried; after step S2 and before step S3, the pyrolytic activated carbon is also washed and then dried.
4. The use according to claim 1, characterized in that: In step S3, the pyrolytic activated carbon is ground and passed through a 50-200 mesh sieve to obtain pyrolytic activated carbon powder.
Citation Information
Patent Citations
Active carbon cement composite material and preparation method thereof
CN101941821A
Phosphoric acid modified coffee residue activated carbon and preparation method thereof
CN112707396A